Television watching time and cognitive development in young children - Anak Agung Ayu Windi Antari; I Gusti Ayu Trisna Windiani; Djauhar Ismail (Indonesian Pediatric Society, 2012)
Background Television viewing for children is prevalent. Therehave been few Indonesian studies on the association betweenduration of television watching and cognitive development inyoung children.Objective To assess cognitive development in young children whowatched < 1 hour, 1-2 hours, or > 2 hours of television daily.Methods We conducted a cross-sectional study at 6 prekindergartensin Denpasar, Bah. We included 135 subjects in thisstudy. Cognitive development was measured by the Mullen ScalesofEarly Learning (MSEL). Data was analyzed by one-way analysisof variance (ANOVA) test, post-hoc test, and univariate analysisof covariance (ANCOVA) with significance level of P < 0.05.Results There were significant differences among compositestandard score in children who watched television < 1 hour, 1-2hours, and> 2 hours per day (P=0.035). The mean compositestandard score in children who watched television 1-2 hours dailywas 6.087 points higher than in those who watched television< 1 hour daily (P=0.013, 95%CI 1.29 to 10.88) and 4.213points higher than in those who watched television > 2 hoursdaily (P=0.045, 95%CI 1.08 to 8.51). There was an associationbetween television watching time and cognitive development(P=0.001).Conclusion Television watching time was statistically associatedwith cognitive development in young children, where thoseviewing television 1-2 hours daily scoring significantly higher thanthose viewing < 1 hour and > 2 hours daily. [Paediatr lndones.2012;52:32-7].